PEMBUATAN RAJUT KONEKTOR MASKER: PENINGKATAN EKONOMI MASA PANDEMI TUBANAN KABUPATEN JEPARA - Susila, Dwi Agus; Wijanarko, Kukuh Dwi; Rosdiana, Aliva; Wakit, Ahmat (Universitas Bunda Mulia, 2022)
Crocheting is one of the hand skills with the method of making clothes or clothing using a single thread as a knitting material and hook. The knitting process must be careful, patient, and concentrated to make creative products. This training was carried out due to the problems faced by participants during the Covid-19 pandemic, namely the loss of creative activities, especially for PKK members, and the loss of confidence in creating new business opportunities. Making crocheting mask connectors is a solution for community service participants. The community service participants consisted of 20 people of PKK members at Tubanan Village, Kembang District, Jepara Regency, Central Java. This training activity is useful for participants to improve and develop crocheting skills as well as an effort to generate business opportunities during the Covid-19 pandemic. Then, the methods used are 1) making a model of work stages, 2) social approach, 3) maximizing partner function, and 4) evaluation of targets. The result of this community service is participants have insight and skills in making crochet mask connectors and in having knowledge of online marketing strategies, either through WhatsApp, Telegram, Instagram, and Facebook. When all promotional media can be carried out properly, there will be positive activities in the form of increasing sales and income, especially during the Covid-19 pandemic.